Physical activity and sport-specific training patterns in Swedish sporting and working trial dogs—A questionnaire survey - Essner, Ann; Hesbach, Amie L.; Igelström, Helena; Kjellerstedt, Catarina; Svensson, Kristina; Westerlind, Helga (Frontiers in Veterinary Science, 2022)
Objective To explore physical activity patterns, including conditioning exercise and sport-specific training, and management routines utilized by handlers of Swedish sporting and working dogs participating in agility, obedience, rally obedience and working trial disciplines. Procedures Dog handlers provided information on competition-level dogs through an internet-based cross-sectional and descriptive survey on physical activity, sport-specific training and management. Results are reported overall and stratified by participation in specific disciplines. Results We received 1615 replies to the questionnaire. After data cleaning, 1582 dogs (98%) remained for the analysis. Of these, 430 participated in agility, 790 in obedience, 596 in rally obedience, and 847 dogs had competed in a working trial, i.e., messenger, protection, search or tracking. Number of disciplines performed by each dog varied between one and five. Most common was participation in one (n = 767, 48%) or two (n = 541, 34%) disciplines. Out of the dogs competing in one discipline, 38% (n = 294) were considered to be specialized as they actively trained only that discipline for ≥10 months per year. The vast majority of the dogs (n = 1129, 71%) received more than 1 h of daily physical activity, e.g., walks, and only n = 51 (3%) were never exercised off-leash. Preferred self-selected gait was trot (n = 907, 57%) and gallop (n = 499, 32%). A fifth (n = 319, 20%) never played with other dogs. The majority (n = 1328, 84%) received more than 1 h of vigorous physical conditioning exercise per week. Almost three quarters (n = 1119, 71%) participated in physical conditioning exercise. Two thirds (n = 953, 60%) participated in at least 3 h of sport-specific training per week and only a very small portion (n = 35, 2%) trained their specific discipline less than once per week. Median total work load, i.e., all daily physical activity, vigorous physical conditioning exercise and sport-specific training, was 16.5 h per week. Conclusion and clinical relevance We observe physical activity at moderate to high durations and moderate to vigorous intensities among Swedish sporting and working trial dogs. Most dogs received physical conditioning exercise, but not all dogs were warmed up before training and competition. Our study provides veterinary professionals and dog trainers with valuable insights on the physical exposures and management routines of sporting and working trial dogs.